Adenomatoid odontogenic tumor - A diagnostic imaging using cone bean computed tomography - Jaishri Pagare; Satyapal Johaley; Jyoti Bhavthankar; Mandakini Mandale (Wolters Kluwer Medknow Publications, 2019)
Adenomatoid odontogenic tumor (AOT) is a rare noninvasive benign tumor of the jaw that originates in the second decade of the life from the odontogenic epithelium without mesenchyme. Radiological examination is an essential component for the diagnosis of benign tumors, the radiographic modality used to acquire the image was speculated to have an effect on the perception of radiopacities, particularly for the cases with minimal intralesional calcifications. Therefore, the capability of radiographic modality in detecting the intralesional calcification was critical for diagnosis of AOT. Cone beam computed tomography (CBCT) provides precise imaging of bony structures with minimal calcification without superimposition and distortion. In this case report, we are reporting a case of AOT of maxilla with characteristic CBCT appearance of AOT of maxilla.